New insights in the treatment of radioiodine refractory differentiated thyroid carcinomas: to lenvatinib and beyond. Issue 7 (August 2015) - Wang, Emilie; Karedan, Tezo; Perez, Cesar A.
Abstract : During the past two decades, several key somatic mutations associated with development and progression of differentiated thyroid cancer (DTC) have been revealed. Historically, the treatment for advanced DTC is challenging after patients become refractory to radioactive iodine. The response to doxorubicin, the only chemotherapy agent approved by the US Food and Drug Administration, is disappointing either as monotherapy or combination therapy. Because of the lack of effective systemic treatment coupled with increased understanding of molecular and cellular pathogenesis, multiple kinase inhibitors (MKIs) as an alternative therapy for the treatment of advanced DTC has generated much interest, enthusiasm, and, most excitingly, promising results. After the encouraging results of these agents in earlier trials, the Food and Drug Administration approved sorafenib for the treatment of locally recurrent, progressive, or metastatic DTC refractory to radioactive iodine treatment based on the results of a multicenter DECISION trial. Sorafenib therefore became the first MKI approved for this indication in more than 20 years. However, even more impressive responses and progression-free survival benefits were seen in the phase III SELECT trial with lenvatinib, giving even higher hopes for the future management of what was considered just a decade ago an orphan disease. Given the role of MKIs, a new era in the treatment of advanced DTC has begun. We review the key therapeutic targets, oncogenic pathways, and promising clinical results of these agents in refractory disease, as well as their roles after failure of first line kinase inhibitors.